The deterministic role of 5-mers in microRNA-gene targeting - Hart, Martin (RNA Biol, 2018)
MiRNAs play a central role in physiological and pathological processes. Both for the biological understanding and for their clinical application, it is essential to understand the interaction of miRNAs and their targets. Target identification largely hinges on in-silico prediction, which requires a complete consideration of miRNA binding sites within the UTRs of target genes. Here, we show that 5-mer sites might also play an essential role for human miRNA-target binding. We implemented and employed an algorithm to all pairs of 2,588 human miRNAs annotated in miRBase and the 3′ UTRs of 16725 genes (>43 million combinations). Our in-silico analysis showed a highly significant enrichment (p = 1.4 × 10(−69)) of 5-mer binding sites in 3′ UTRs across all experimentally validated miRNA-target gene pairs. We next confirmed the central role of 5-mer binding sites by reporter assays and demonstrated that two non-canonical 5-mer sites of miR-34a in the 3′ UTR of T-cell receptor alpha (TCRA) have a significantly stronger influence on its posttranscriptional regulation than the canonical binding sites. These observations indicate an essential role of 5-mer binding sites for the miRNA targeting in human cells.